Exploring the associations of gut microbiota with inflammatory and the early hematoma expansion in intracerebral hemorrhage: from change to potential therapeutic objectives - Jiang, Haixiao; Zeng, Wei; Zhu, Fei; Zhang, Xiaoli; Cao, Demao; Peng, Aijun; Wang, Hongsheng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAlthough a great deal of research has explored the possibility of a systemic inflammatory response and dysbiosis of the gut microbiota after an intracerebral hemorrhage (ICH), the relationships between gut microbiota and blood inflammatory indicators as well as their role in the hematoma expansion following an early-stage mild-to-moderate ICH (emICH) remain unknown. This study analyzes these changes and associations in order to predict and prevent hematoma expansion after emICH.MethodsThe study included 100 participants, with 70 individuals diagnosed with emICH (30 with hematoma expansion and 40 without hematoma expansion, referred to as the HE and NE groups) and 30 healthy controls matched in terms of age and gender (HC). We used 16S rRNA gene sequencing to explore the gut microbial structure and its underlying associations with blood inflammatory parameters in the HE group.ResultsOur findings showed a significant decrease in the diversity and even distribution of microorganisms in the HE group when compared to the HC and NE groups. The composition of the gut microbiota experienced notable alterations in the emICH group, especially in HE. These changes included a rise in the number of gram-negative pro-inflammatory bacteria and a decline in the level of probiotics. Furthermore, we observed strong positive connections between bacteria enriched in the HE group and levels of systemic inflammation. Several microbial biomarkers (e.g. Escherichia_Shigella, Enterobacter, and Porphyromonas) were revealed in disparateiating HE from HC and NE. Analysis of the Kyoto Encyclopedia of Genes and Genomes (KEGG) exposed disturbances in essential physiological pathways, especially those related to inflammation (such as the Toll-like receptor signaling pathway), in the HE group.ConclusionsOur exploration indicated that individuals with emICH, especially those with HE, demonstrate notably different host-microbe interactions when compared to healthy individuals. We deduced that emICH could rapidly trigger the dysbiosis of intestinal flora, and the disturbed microbiota could, in turn, exacerbate inflammatory response and increase the risk of hematoma expansion. Our comprehensive research revealed the potential of intestinal flora as a potent diagnostic tool, emphasizing its significance as a preventive target for HE.